Managing Foreign Exchange Exposure (Book). - Hendrickson, Harvey S.; Radebaugh, Lee H. (The Accounting Review, 1986)
Abstract Reviews the book "Managing Foreign Exchange Exposure," by Donald H. Drury and Vihang R. Errunza.